Pengujian Pupuk Organik Agen Hayati (Trichoderma sp) terhadap Pertumbuhan Kentang (Solanum tuberosum L) - Laurensius Lehar (Jurnal Penelitian Pertanian Terapan, 2012)
he use of organic fertilizer and a biology agent called Trichoderma sp can be applied to reduce high cost production. The aim of the experiment was to compare the use of the biology agent (Trichoderma sp) with fungicide and organic fertilizer and non-organic fertilizer and their interactions. This experiment used Divisible Check Device (RPT) consisting of two factors namely Trichoderma sp and inorganic fungicide as a main factor and the other factor as a minor factor consisting of chicken dirt, cow dirt, kana liquid organic fertilizer, complex liquid organic fertilizer, and standard NPK fertilizer. The result of the experiment shows that there is an interaction between the use of Trichoderma sp with various kinds of fertilizers towards the height of plants from age 4-10 mst, the number of leaf at the age of 6,8 and 10 mst, wide index of the leaf at the age of 6 mst and 6 mst along with the number of branch at the age of 4 mst. Keywords: organic fertilizer,trichoderma sp, potato.